Decoding reality : the universe as quantum information - Vedral, Vlatko (Oxford, U.K. : Oxford University Press, 2018)
Theoretical physicist Vlatko Vedral comments on the concept of information and the creation of reality, discussing the idea of entropy, the bizarre effects of quantum behavior, the origins of all the information in the universe, and other topics.
Includes bibliographical references (p. 219-225) and index.
Adult
Adult
Keywords: Information theory; Physics -- Philosophy; Quantum computers; Quantum theory; Space and time; Information theory; Physics -- Philosophy; Quantum computers; Quantum theory; Space and time